5+6(x-8)=8-9(x-6)

Simple and best practice solution for 5+6(x-8)=8-9(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+6(x-8)=8-9(x-6) equation:


Simplifying
5 + 6(x + -8) = 8 + -9(x + -6)

Reorder the terms:
5 + 6(-8 + x) = 8 + -9(x + -6)
5 + (-8 * 6 + x * 6) = 8 + -9(x + -6)
5 + (-48 + 6x) = 8 + -9(x + -6)

Combine like terms: 5 + -48 = -43
-43 + 6x = 8 + -9(x + -6)

Reorder the terms:
-43 + 6x = 8 + -9(-6 + x)
-43 + 6x = 8 + (-6 * -9 + x * -9)
-43 + 6x = 8 + (54 + -9x)

Combine like terms: 8 + 54 = 62
-43 + 6x = 62 + -9x

Solving
-43 + 6x = 62 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-43 + 6x + 9x = 62 + -9x + 9x

Combine like terms: 6x + 9x = 15x
-43 + 15x = 62 + -9x + 9x

Combine like terms: -9x + 9x = 0
-43 + 15x = 62 + 0
-43 + 15x = 62

Add '43' to each side of the equation.
-43 + 43 + 15x = 62 + 43

Combine like terms: -43 + 43 = 0
0 + 15x = 62 + 43
15x = 62 + 43

Combine like terms: 62 + 43 = 105
15x = 105

Divide each side by '15'.
x = 7

Simplifying
x = 7

See similar equations:

| 3x(-4x-3)(3-x)= | | 4(2a+1)=2(a+2)+5 | | 6x+38=15x-34 | | 8t+7t=120 | | 11x-29=5x+1 | | 5x^2+8x-4=0 | | 14-y=-18+7y | | z=y+12 | | -8t=16 | | 12x+9=7x+29 | | 7=14+x | | -2y=x+7 | | 8x-15=81 | | d=3h | | (x+3)2-7(x+3)+10=0 | | 6x^9y^7+18x^7y^6+42xy=0 | | 2b-8=b+7 | | 9x^9y^7+18x^7y^6+42xy=0 | | 7x+2+6x+7=12x+5 | | 2x=5+5y | | 3.5x-0.5=3 | | 4x^3+6x^2-12x-2=0 | | 3(7x)=105 | | 45x^2-6x-24=0 | | x-12=-8+2x | | (Y^2-7y)(y-5)= | | 6x+5=85-4x | | 6-5(3x-2)=-44 | | n=0.04x-78.50 | | 5-4(x+3)=5 | | 3-y=2x | | (y^2-7x)(y-5)= |

Equations solver categories